(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, showing that, it is possible to analyze texts and break through the deliberate clouding of meaning, based on text analysis and is give reliable conclusions. The main goal of this article is to explain how political texts are structured, to show how they can be analyzed and what information can be extracted from them. In the last few decades, the study of political communication has expanded greatly, and this growth has been evident around the world. This article will be basic information about some characteristic features of political texts.